Conformational Disorder Enhances Solubility and Photovoltaic Performance of a Thiophene–Quinoxaline Copolymer. Issue 6 (25th February 2013) - Wang, Ergang; Bergqvist, Jonas; Vandewal, Koen; Ma, Zaifei; Hou, Lintao; Lundin, Angelica; Himmelberger, Scott; Salleo, Alberto; Müller, Christian; Inganäs, Olle; Zhang, Fengling; Andersson, Mats R.
Abstract The side‐chain architecture of alternating copolymers based on thiophene and quinoxaline (TQ) is found to strongly influence the solubility and photovoltaic performance. In particular, TQ polymers with different linear or branched alkyloxy‐phenyl side chains on the quinoxaline unit are compared. Attaching the linear alkyloxy side‐chain segment at the meta‐ instead of the para‐position of the phenyl ring reduces the planarity of the backbone as well as the ability to order. However, the delocalisation across the backbone is not affected, which permits the design of high‐performance TQ polymers that do not aggregate in solution. The use of branched meta‐(2‐ethylhexyl)oxy‐phenyl side‐chains results in a TQ polymer with an intermediate degree of order. The reduced tendency for aggregation of TQ polymers with linear meta‐alkyloxy‐phenyl persists in the solid state. As a result, it is possible to avoid the decrease in charge‐transfer state energy that is observed for bulk‐heterojunction blends of more ordered TQ polymers and fullerenes. The associated gain in open‐circuit voltage of disordered TQ:fullerene solar cells, accompanied by a higher short‐circuit current density, leads to a higher power conversion efficiency overall. Thus, in contrast to other donor polymers, for TQ polymers there is no need to compromise between solubility and photovoltaic performance.